FRI0225 Anemia is a better predictor for radiographic damage in rheumatoid arthritis than das28 when determined before start of tocilizumab-treatment – a secondary analysis from the act-ray trial. (15th June 2017) - Möller, B; Scholz, G; Dougados, M; Huizinga, T; Villiger, PM; Finckh, A
Abstract : Background: Clinical remission, or at least low disease activity, as measured by DAS28 or alternative compound indices is currently the goal of RA treatment. Anemia in the context of RA is mainly driven by tumor necrosis factor alpha (TNF-α) and interleukin-six (IL-6), and may serve as a simple biological marker of inflammation. Anemia was recently discovered as a largely DAS28-independent parameter to predict radiographic damage progression in RA, both with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) or with anti-TNF agents. Objectives: To study the predictive value of anemia in relation to DAS28 for radiographically detectable joint damage progression in patients treated with IL-6R inhibitor tocilizumab (TCZ) plus conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) when used in a treat to target concept. Methods: In the ACT-RAY trial, all patients were methotrexate (MTX) inadequate responders and randomized to receive either TCZ plus MTX (add-on) or TCZ plus placebo (switch strategy) for at least one year. After week 24, open-label csDMARDs other than MTX could be added according to a treat-to-target approach in patients with moderate or high disease activity (DAS28≥3.2). After week 52, patients in sustained clinical remission (DAS28<2.6) could discontinue TCZ before stopping csDMARDs, and finally MTX/Placebo. The exposure of interest was anemia, defined using the WHO definition or the more liberal NHANES definition, both at baseline and over time. The primary outcome was the rate of joint damage progression measured by the change in the modified total Sharp score (ΔmTSS). We used longitudinal multivariate mixed effects models to test the impact of anemia on ΔmTSS. To examine the association of anemia to ΔmTSS independently from RA disease activity, the models were run with and without DAS28 at baseline and DAS28 over time. Results: Of 556 randomised patients, complete datasets for fully adjusted models were available from 285 patients. Overall radiographic progression was regarded to be minimal, with insignificant differences in favor of the add-on strategy. Median annual ΔmTSS before inclusion was 2.9 (IQR 1.5 to 6.4) in patients without and 5.5 (IQR 2.7 to 11.1) in patients with baseline anemia, but evolved subsequently similar when being on TCZ. Anemia at baseline was a strong predictor of mTSS (per WHO definition: coefficient 14.8, 95% CI 7.6–21.9, p<0.001; per NHANES definition: coefficient 14.6 95% CI 7.6–21.5 p<0.001), as well as baseline DAS28 (coefficient 3.9, 95% CI 0.7–7.0, p=0.016). Mean DAS28 over time (p<0.001), in contrast to anemia data over time when obtained in patients already on TCZ, was significantly associated with subsequent ΔmTSS. Baseline anemia in contrast to baseline DAS28 remained a significant predictor of mTSS for up to two years on TCZ in fully adjusted multivariate analyses (p<0.05), including time-variant DAS28. Conclusions: Anemia may be a strong and DAS28-independent long-term predictor of radiographic joint damage progression. Present data from patients on IL-6R blockade, a potent target-specific RA treatment with major impact also on erythropoiesis, add importantly to the growing body of evidence for the studied association. Disclosure of Interest: None declared